2017
DOI: 10.1002/lsm.22673
|View full text |Cite
|
Sign up to set email alerts
|

A new path in defining light parameters for hair growth: Discovery and modulation of photoreceptors in human hair follicle

Abstract: We provide the first evidence that (i) OPN2 and OPN3 are expressed in human hair follicle, and (ii) A 453 nm blue light at low radiant exposure exerts a positive effect on hair growth ex vivo, potentially via interaction with OPN3. Lasers Surg. Med. 49:705-718, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 68 publications
(109 reference statements)
3
91
0
1
Order By: Relevance
“…In contrast, the expression of OPN3 (with an absorption peak at a longer wavelength of 460 nm) was mainly confined to the stratum basale, albeit lower expression was also seen in the suprabasal layer. This is partially in agreement with localization of OPN3 in human scalp , where expression was higher in differentiated layers of the epidermis compared to facial or abdominal skin in this study. The expression of OPN3 in basal keratinocytes may be explained by its absorption at a slightly longer wavelength (465 nm) , compared to OPN1‐SW .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the expression of OPN3 (with an absorption peak at a longer wavelength of 460 nm) was mainly confined to the stratum basale, albeit lower expression was also seen in the suprabasal layer. This is partially in agreement with localization of OPN3 in human scalp , where expression was higher in differentiated layers of the epidermis compared to facial or abdominal skin in this study. The expression of OPN3 in basal keratinocytes may be explained by its absorption at a slightly longer wavelength (465 nm) , compared to OPN1‐SW .…”
Section: Discussionsupporting
confidence: 92%
“…In parallel with this in vitro and clinical work focusing on combating PV and AD, ex vivo studies on human hair follicles and in vitro studies on outer root sheath keratinocytes demonstrated positive effects of low‐fluence (<5 J/cm 2 ) blue light on the prolongation of the anagen phase and on the proliferation of hair follicle matrix keratinocytes . Low‐fluence blue light was also reported to have a stimulatory effect on the metabolism of human dermal fibroblasts, leading to increased production of collagen, whereas higher levels had an inhibitory effect on cell metabolism and protein synthesis .…”
Section: Introductionmentioning
confidence: 76%
“…While perhaps the vast majority of applications focuses on red and NIR wavelengths, UV‐free blue light, corresponding to the spectral range of both violet (400‐450 nm) and blue (450‐495 nm), has been attracting increasing attention. A solid body of scientific data has been accumulated in the last decade, stemming from in vitro experiments on human cutaneous cells performed using well‐defined irradiation parameters . The current evidence attributes the high therapeutic potential of UV‐free 453 nm blue light to its antiproliferative capacity on human endothelial cells, keratinocytes, and fibroblasts, often ascribed to initiation of cell differentiation triggered by the release of nitric oxide (NO) from nitrosated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, cytochrome c oxidase and nitrozated proteins were considered as the major targets of light . Recently, there has been increasing evidence that cryptochromes and opsins , mediate the cell's response to visible and UV light. All this suggests that there are several molecular targets, which could intercept a photon of light and trigger multiple signaling cascades.…”
Section: Introductionmentioning
confidence: 99%